Common Institutional Ownership and Earnings Management. (28th November 2020) - Ramalingegowda, Santhosh; Utke, Steven; Yu, Yong
ABSTRACT: This study examines the relation between earnings management and block ownership of same‐industry peer firms by a common set of institutional investors (common institutional ownership). This relation is important given the tremendous growth of common institutional ownership and the significant influence of blockholders on financial reporting. We hypothesize that common institutional ownership mitigates earnings management by enhancing institutions' monitoring efficiency and by encouraging institutions to internalize the negative externality of a firm's earnings management on peer firms' investments. Consistent with our hypothesis, we find that higher common institutional ownership is related to less earnings management. Analyses of a quasi‐natural experiment based on financial institution mergers show that this negative relation is unlikely to be driven by the endogeneity of common institutional ownership. Cross‐sectional tests provide evidence that the negative relation is stronger among firms for which common institutional ownership is likely to generate a greater reduction in institutions' information acquisition and processing costs, and among firms whose severe financial misstatements are more likely to distort co‐owned peer firms' investments, supporting both mechanisms underlying our hypothesis. Our findings inform the ongoing debate on the costs and benefits of common institutional ownership by highlighting an important benefit: the enhanced monitoring of financial reporting. RÉSUMÉ: Propriété commune par des investisseurs institutionnels et gestion des résultats La présente étude examine la relation entre la gestion des résultats et la détention commune de blocs d'actions de sociétés paires d'un même secteur d'activités par un ensemble d'investisseurs institutionnels (propriété commune). Cette relation est importante, compte tenu de l'énorme croissance de la propriété commune et de l'influence des détenteurs de blocs d'actions sur la communication de l'information financière. Nous présumons que la propriété commune réduit la gestion des résultats en augmentant l'efficacité du contrôle des institutions et en encourageant celles‐ci à internaliser l'externalité négative de la gestion des résultats d'une firme sur les investissements des firmes paires. Conformément à notre hypothèse, nous établissons qu'un haut niveau de propriété commune est lié à une gestion des résultats moindre. Des analyses d'une expérience quasi naturelle fondée sur des fusions d'institutions financières montrent que cette relation négative n'est pas susceptible d'être stimulée par l'endogénéité de la propriété commune. Des analyses transversales fournissent des données probantes indiquant que la relation négative est plus marquée chez les sociétés pour lesquelles la propriété commune est susceptible de générer une réduction plus importante des coûts d'acquisition et de traitement de l'information assumés par les institutions, de même que chez celles dont des déclarations financières inexactes graves sont plus susceptibles de fausser les investissements des sociétés paires en copropriété, à l'appui des deux mécanismes qui sous‐tendent notre hypothèse. Nos observations éclairent le débat en cours sur les coûts et avantages de la propriété commune en mettant en lumière un avantage important, soit un meilleur contrôle de la communication de l'information financière.